Helminth communities of endemic cyprinoids of the Apennine Peninsula, with remarks on ectoparasitic monogeneans, and a description of four new Dactylogyrus Diesing, 1850 species - Benovics, Michal; Francová, Kateřina; Volta, Pietro; Dlapka, Vojtěch; Šimková, Andrea (Parasitology, 2021)
The fauna of the Apennine Peninsula is, in comparison to other southern European peninsulas, relatively species-poor regarding the number of endemic cyprinoid species. Nonetheless, the recent introduction of non-native species has significantly increased the total number of freshwater species in this region. Such invasive species may represent a threat to the native fauna, associated among other things with the introduction of non-native parasites with their original hosts.In the present study, we investigated endemic cyprinoid species for the presence of helminth parasites. A total of 36 ectoparasitic monogenean species and five endoparasitic helminth species were collected from ten cyprinoid species in five localities in northern Italy. Out of 20 Dactylogyrus species (gill monogeneans specific to cyprinoids), four were identified as new to science and herein described: Dactylogyrus opertus n. sp. and Dactylogyrus sagittarius n. sp. from Telestes muticellus, Dactylogyrus conchatus n. sp. from T. muticellus and Protochondrostoma genei, and Dactylogyrus globulatus n. sp. from Chondrostoma soetta. All new Dactylogyrus species appear to be endemic to the Apennine Peninsula; however, they share a common evolutionary history with the endemic Dactylogyrus parasitizing cyprinoids of the Balkans. This common origin of cyprinoid-specific parasites supports a historical connection between these two (currently separated) geographical regions.
Keywords: Italy; Cyprinoidei; Gills; Killifishes; žábry; Cyprinodontidae; Helminthiasis, Animal; genetická variace; Italian Peninsula; DNA, Helminth; cizopasní červi; helmintózy zvířat; řeky; Rivers; Ectoparasitic Infestations; taxonomy; Genetic Variation; zvířata; parasite diversity; nemoci ryb; infestace ektoparazity; DNA helmintů; fylogeneze; Trematoda; Itálie; Fish Diseases; Helminths; phylogeny; Phylogeny; endemic species; Animals